Fuzzy multiobjective decision support model for urban rail transit projects in China - Zhao, Jinbao; Deng, Wei (Transport, 2013)
This paper aims at developing a fuzzy multiobjective decision support model for urban rail transit projects in China under the background that China is presently experiencing an unprecedented construction of urban rail transit. In this study, an appropriate model using multilevel fuzzy comprehensive evaluation is developed. To do so, detailed description and definition of multilevel fuzzy comprehensive evaluation is displayed. In the decision process, the followings are considered as the influential objectives: traveller attraction, environment protection, project feasibility and operation. In addition, consistent matrix analysis method is used to determine the weights between objectives and the factor weights between factors, which reduce the work caused by repeated establishment of the decision matrix on the basis of ensuring the consistency of decision matrix. An application study is provided as an example to demonstrate the feasibility of this model. The results show that this model is reliable and applicable for decisionmaking in urban rail transit projects. Finally, a decision support system is developed to benefit decisionmakers in optimizing the process of identifying superior urban rail transit projects.First Published Online: 11 Oct 2013